Can patient gratitude expression boost innovative performance? The role of work meaningfulness and supervisory support - Liu, Bing; Liu, Mengli; Wang, Huijuan; Yang, Yuanqi; Ma, Ying; Wei, Xin (Frontiers in Psychology, 2022)
Based on emotions as social information theory, the current study proposed how and when patient gratitude expression could promote nurses’ innovative performance. Using a time-lagged data of 649 nurses from three class A tertiary 12 hospitals in China, the results showed that patient gratitude expression was positively related to nurses’ innovative performance, and nurses’ work meaningfulness mediated such effect. Furthermore, supervisory support moderated the relationship of work meaningfulness with nurses’ innovative performance, as well as the indirect relationship between patient gratitude expression and innovative performance through work meaningfulness, such that the indirect relationship was stronger when supervisory support is higher. Our research helps to expand our understanding of how patient gratitude expression as an organizational external factor influences nurses’ innovation in health care, and meanwhile, provides management insights for hospital managers to focus on patient gratitude expression and enhance nurse innovation.